Analisis Perbandingan Kinerja Algoritma Huffman Dan Algoritma Levenstein Dalam Kompresi File Dokumen Format .RTF - Dwi Asdini; Dito Putro Utomo (STMIK Budi Darma, 2022)
Document files with the .RTF format are files that are quite often used but have a fairly large size. Large file sizes often experience problems when sending files where the sending process can take a long time and can consume a lot of storage space because too much large data is stored. This is certainly very difficult if there are many files that must be stored, while the storage media has a size limit. To overcome this problem it is necessary to do compression to compress the data. To choose the optimal algorithm for compressing document files, it is necessary to compare the Huffman algorithm and the Levenstein algorithm by measuring performance based on the Ratio Of Compression (RC), Compression Ratio (CR), Redundancy (Rd) and Space Saving (SS). After the calculation, the results of the most optimal algorithm in compressing document files are obtained, namely the Huffman algorithm with higher space saving and lower compression results compared to the Levenstein algorithm. This is because the greater the space saving (ss) the compression is getting better and faster.